Vice-Chancellor launches UMP’s 2011-2015 Strategic Planning - UMP, PNC
With a longterm vision to become the “first choice world class technological university”, Universiti Malaysia Pahang (UMP) has to execute a holistic campus-wide transformation, a migration of human capital attitude and a careful drawing up of strategic planning, said Vice-Chancellor Professor Dato’ Dr Daing Nasir Daing Ibrahim.